Financial markets and institutions - Mishkin, Frederic S. (Addison-Wesley series in finance, 1999)
Fast becoming a market leader, the text emphasizes basic principles and organizes students' thinking about the structure, function, and management of markets and institutions. Whereas other texts are highly descriptive, Financial Markets and Institutions incorporates the financial practitioner's approach through its emphasis on an applied managerial perspective For the UG and MBA course in Financial Markets and Institutions and Money and Capital markets.sian financial crises, recent developments in financial consolidation, the newly-created European Central Bank, and the U.S. debate over social security.